Republic of Poland : Arrangement Under the Flexible Credit Line and Cancellation of the Current Arrangement-Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
Poland's economy has recovered well in 2010-11, reflecting strong economic fundamentals and decisive countercyclical policies. Poland's strong trade and financial links to Europe continue to make it vulnerable to potential shocks from the region. Despite the difficult external environment, the authorities have continued to rebuild policy space to counter adverse shocks. Measures are also being taken to strengthen medium- and long-term fiscal sustainability. The economy is expected to moderate further in 2013. Financial sector policies have helped improve the resilience of the banking system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet